Toward Better Preparedness of Mediterranean Rainfed Agricultural Systems to Future Climate-Change-Induced Water Stress: Study Case of Bouregreg Watershed (Morocco) - Brouziyne, Youssef; Abouabdillah, A.; Bouchaou, L.; Attar, O.; Ez-zaouy, Y.; Benaabidate, L.; Chehbouni, Abdelghani (MDPI, 2022)
Improving the preparedness of agricultural systems to future climate-change-induced phenomena, such as drought-induced water stress, and the predictive analysis of their vulnerability is crucial. In this study, a hybrid modeling approach based on the SWAT model was built to understand the response of major crops and streamflow in the Bouregreg catchment in Morocco to future droughts. During dry years, the simulation results showed a dramatic decrease in water resources availability (up to −40%) with uneven impacts across the study catchment area. Crop-wise, significant decreases in rainfed wheat productivity (up to −55%) were simulated during future extremely dry growing seasons.